Creative approaches to poetry for the primary framework for literacy [ - Foale, Jan; Pagett, Linda (Routledge, 2009)
Supports teachers in planning, teaching and enjoying poetry with their pupils. With an emphasis on creative, cross curricular approaches, this book explores methods of teaching poetry in an engaging